Non-medical Use of Prescription Gabapentinoids (Gabapentin and Pregabalin) in Five European Countries - Fonseca, Francina; Lenahan, William; Dart, Richard C.; Papaseit, Esther; Dargan, Paul I.; Wood, David M.; Guareschi, Marilena; Maremmani, Icro; Auriacombe, Marc; Farré, Magí; Scherbaum, Norbert; Torrens, Marta (Frontiers in Psychiatry, 2021)
Background: Non-medical use (NMU) of prescription GABA analogues (pregabalin and gabapentin) has been reported especially in opiate dependent persons. However, by now the prevalence of NMU of gabapentinoids in the general population has not been sufficiently evaluated. The aim of this research paper is to determine the prevalence of prescription GABA analogue NMU and associated demographics in five European countries with special detail of Spain. Methods: The RADARS Survey of Non-Medical Use of Prescription Drugs Program (NMURx) is a harmonized series of contemporaneous cross-sectional surveys of adults conducted in multiple countries. NMURx collects data from the general population in each participating country about NMU of prescription drugs, illicit drugs, and associated demographics. NMU was defined as “using a medication without a doctor’s prescription or for any reason other than what was recommended by their doctor.” Responses from Spain (4Q2017, n=10,062) were analyzed in detail. Comparative data were available from France, Germany, Italy, and UK. Responses were collected using non-probability quota sampling and post-stratification population weighting was applied to reflect the national distributions of adults, based on age, gender, and census region. Rates of NMU and associated demographics were reported as rate of past 90-day NMU per 100,000 adult population with 95% confidence intervals. Results: Germany (1,197 per 100,000 adult population [95% CI: 1,004.3-1,379.1]) and United Kingdom (1,067 per 100,000 adult population [95% CI: 851.3-1,283.2]) presented the highest prevalence of gabapentinoids NMU. In Spain the prevalence of past 90 days GABA analogue NMU was: 344.4, 95% (CI 204.8-484.0), with male predominance. Those who non-medically use GABA analogues had a higher prevalence of lifetime chronic pain, lifetime illicit drug use, and previous substance abuse treatment. In Spain, 20% of respondents who ever have used gabapentinoids, reported a lifetime NMU; the prevalence was higher for pregabalin 624 (6.2%) than for gabapentin 444 (4.4%). The main reasons for use were to self-treat pain and other medical conditions. Conclusions: The risk of NMU of gabapentinoids should not to be neglected. Subjects with a history of chronic pain and lifetime substance use disorders had an increased risk of NMU of gabapentinoids.